Assessing the effect of oral diseases on oral health related quality of life of institutionalized elderly using Oral Health Impact Profile (OHIP-14) questionnaire: a pilot study - Antima Saxena; Ramesh Nagarajappa; Debasruti Naik; Mohammed Abid; Gayathri Ramesh (Roczniki Panstwowego Zakladu Higieny, 2020)
Background. India establishes a geriatric population of about 80 million which is 7.2% of the total population. The geriatric population is often faced by a negative impact on their quality of life due to poor oral health. Objectives. To assess the impact of oral disease on daily activities and quality of life among the institutionalized elderly in Kanpur, India. Materials and Method. A total of fifty-six patients were purposively selected from two old age homes through convenience sampling technique. To assess the oral health status WHO basic oral health survey form (1997) was used. Short version of Oral Health Impact Profile (OHIP - 14) questionnaire was used to assess the Oral Health Related Quality of Life (OHRQoL). Independent t-test and ANOVA test was done to determine the relationship between the groups. Results. Presence or absence of grossly decayed teeth, chronic periodontitis, based on edentulism and remaining sound teeth status produced no significant differences in any of the domains. In comparison with males, females experienced greater impact of oral diseases with respect to mean OHIP-14 score; however, it was non – significant (p=0.45). Conclusion. Oral health status of the institutionalized subjects in Kanpur city is poor, with edentulism and periodontitis. The effect of oral diseases on the lives of elderly is comparatively low and is non-significant.